\(\dfrac{2^7\cdot25^4}{10^8}+\dfrac{-1}{5}+\left(-1.98765\right)^0\)
\(=\dfrac{2^7\cdot5^8}{2^8\cdot5^8}+\dfrac{-1}{5}+1\)
\(=\dfrac{1}{2}-\dfrac{1}{5}+1\)
\(=\dfrac{13}{10}\)
\(\dfrac{2^7\cdot25^4}{10^8}+\dfrac{-1}{5}+\left(-1.98765\right)^0\)
\(=\dfrac{2^7\cdot5^8}{2^8\cdot5^8}+\dfrac{-1}{5}+1\)
\(=\dfrac{1}{2}-\dfrac{1}{5}+1\)
\(=\dfrac{13}{10}\)
Bài 1:
a,\(3^7\) : \(3^5\)- \(\left(\dfrac{5}{17}\right)^0\) b,\(\left(\dfrac{5}{2}\right)^{13}\) : \(\left(\dfrac{1}{2}+2\right)^3\) c, 8.\(\left(\dfrac{1}{4}\right)^3\) +\(\left(\dfrac{2}{27}\right)^0\) - \(\dfrac{1}{8}\)
Bài 2 :
a, \(\dfrac{3^4.4^4}{6^4}\) b,\(\dfrac{15^3}{10^3}\) c, \(\dfrac{4^2.12^5}{9^2.2^{10}}\) d, \(\dfrac{6^2+5.2^2+4}{15}\)
Bài 3 :
a, \(\dfrac{\left(\dfrac{2}{3}\right)^3.\left(\dfrac{-3}{4}\right)^2.\left(-1\right)^5}{\left(\dfrac{2}{5}\right)^2.\left(\dfrac{-5}{12}\right)^2}\) b,\(\dfrac{6^6+6^3.3^3+3^6}{-73}\)
Mọi người giúp mình nhé mình sẽ cho bạn 1 like
2. Tìm x
a. \(\dfrac{4}{5}-3.\left|x\right|=\dfrac{1}{5}\) b. \(4x-\dfrac{1}{2}x+\dfrac{3}{5}x=\dfrac{4}{5}\)
c. (2x-8)(10-5x)=0 d. \(\dfrac{3}{4}+\dfrac{1}{4}\left|2x-1\right|=\dfrac{7}{2}\)
\(\dfrac{8^{14}}{4^4.64^5}\)
\(\dfrac{9^{10}.27^7}{81^7.3^{15}}\)
\(\left(\dfrac{3}{10}\right)^4.\left(0,3\right)^5.\left(\dfrac{10}{3}\right)^{10}\)
\(\dfrac{\left(4^3\right)^2.9^4}{6^7.8^2}\)
\(\dfrac{4^8.9^4}{6^6.8^3}\)
\(3^6.\left(\dfrac{1}{3}\right)^6.81^2.\dfrac{1}{27^2}\) TÍNH
a)\(\dfrac{-5}{8}-2.\dfrac{25}{10}+\dfrac{1}{2}\)
b)\(4\dfrac{5}{9}:\left(\dfrac{-5}{7}\right)+5\dfrac{4}{9}:\left(\dfrac{-5}{7}\right)\)
tìm x,y biết:
a) \(x^2+\left(y-\dfrac{1}{10}\right)^4=0\)
b) \(\left(\dfrac{1}{2}.x-5\right)^{20}+\left(y^2-\dfrac{1}{4}\right)^{10}\le0\)
Tìm x
\(a,3-x=x+1,8\)
\(b,2x-5=7x+35\)
\(c,2\left(x+10\right)=3\left(x-6\right)\)
\(d,8\left(x-\dfrac{3}{8}\right)+1=6\left(\dfrac{1}{6}+x\right)+x\)
\(e,\dfrac{2}{9}-3x=\dfrac{4}{3}-x\)
\(g,\dfrac{1}{2}x+\dfrac{5}{6}=\dfrac{3}{4}x-\dfrac{1}{2}\)
\(h,x-4=\dfrac{5}{6}\left(6-\dfrac{6}{5}x\right)\)
\(k,7x^2-11=6x^2-2\)
\(m,5\left(x+3.2^3\right)=10^2\)
\(n,\dfrac{4}{9}-(\dfrac{1}{6^2})=\dfrac{2}{3}\left(x-\dfrac{2}{3}\right)^2+\dfrac{5}{12}\)
\(10\dfrac{1}{4}\div\left(\dfrac{-3}{5}\right)-8\dfrac{1}{4}\div\left(\dfrac{-3}{5}\right)\) tính
Tìm x :
1) \(\left(-0,75x+\dfrac{5}{2}\right).\dfrac{4}{7}-\left(-\dfrac{1}{3}\right)=-\dfrac{5}{6}\)
2) \(\left(4x-9\right)\left(2,5+\dfrac{-7}{3}x\right)=0\)
3) \(\left|x-\dfrac{3}{4}\right|-\dfrac{1}{2}=0\)
4)\(\left(\dfrac{3}{5}-\dfrac{2}{3}x\right)^3=\dfrac{-64}{125}\)
\(d,\dfrac{\left(13\dfrac{1}{4}-2\dfrac{5}{27}-10\dfrac{5}{6}\right).230\dfrac{1}{25}+46\dfrac{3}{4}}{\left(1\dfrac{3}{7}+\dfrac{10}{3}\right):\left(12\dfrac{1}{3}-14\dfrac{2}{7}\right)}\)